Application of numerical simulation method to improve shear strength and rutting resistance of asphalt mixture. Issue Volume 21:Issued 1(2020) (2nd January 2020) - Ji, Xiaoping; Jiang, Yingjun; Zou, Haiwei; Cao, Fan; Hou, Yueqin
Abstract: The interlocking force of aggregates, which is closely related to mixture gradation, is one of the main factors that influence the shear strength and rutting resistance of an asphalt mixture. Gradation is optimised by traditional methods, including the step-filling test and experimental tests on shear strength such as the uniaxial penetration test (UPT). However, both methods have disadvantages. Thus, research has focused on a virtual method based on the numerical simulation method (NSM). Here, a visual method for the UPT based on the NSM (UPT–NSM) is developed, which optimises the mixture gradation to improve the shear strength and rutting resistance of asphalt mixtures. The UPT–NSM results are consistent with those of an indoor test, with an error of less than 4%, thus proving the reliability of the UPT–NSM. From the perspective of the aggregate fraction, using the UPT–NSM can optimise the gradation better than the step-filling test in order to improve the shear strength and rutting resistance of the asphalt mixture. The anti-shear strength and dynamic stability of the asphalt mixture with gradation optimised by UPT–NSM are 25.5 and 27.0% higher, respectively, than those of the specified gradation.